2021
DOI: 10.1001/jamanetworkopen.2021.28561
|View full text |Cite|
|
Sign up to set email alerts
|

Patient Perceptions and Knowledge of Ionizing Radiation From Medical Imaging

Abstract: IMPORTANCE Although imaging has become a standard tool of modern medicine, its widespread use has been paralleled by an increasing cumulative radiation dose to patients despite technological advancements and campaigns calling for better awareness and minimization of unnecessary exposures. OBJECTIVETo assess patients' knowledge about medical radiation and related risks. DESIGN, SETTING, AND PARTICIPANTSA survey study of hospitals in Italy was conducted; all patients in waiting rooms for medical imaging procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 35 publications
0
18
0
4
Order By: Relevance
“…For each vascular segment of interest, we choose two images from different angles for reconstruction, each of which is a single static 512 × 512 image and its frame rate is 66.67. These images are usually generated by XRA and may pose a risk of radiation exposure [24].…”
Section: Resultsmentioning
confidence: 99%
“…For each vascular segment of interest, we choose two images from different angles for reconstruction, each of which is a single static 512 × 512 image and its frame rate is 66.67. These images are usually generated by XRA and may pose a risk of radiation exposure [24].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, a datum seen as an occult sign of neoplasm could determine an economic waste linked to the execution of various radiological investigations, even very expensive, for the search for a tumour that probably does not exist. Radiological examinations that often involve the use of ionizing radiation, with known effects on the health of citizens [ 47 , 48 ], should be optimize ensuring the lowest reasonably achievable exposure levels (ALARA principle) [ 49 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, radiographers should have familiarity and understanding of clinical examinations to preserve the low risk of radiation without compromising the diagnostic accuracy of pediatric radiographs [ 5 , 6 ]. Moreover, several studies have reported that patients undergoing diagnostic X-ray examinations tend to have limited knowledge about medical radiation and its associated risks [ 7 ]. Therefore, it is necessary to optimize and estimate the radiation dose with the goal of alleviating induced biological effects, especially in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%